BUTA KORTIKAL PASCA INJEKSI HISTOACRYL - Aida Fithrie, Freddy Sitorus> (Neurona Majalah Kedokteran Neuro Sains, 2013)
WE REPORT A 25YEAROLD MALE WITH SUDDEN BLINDNESS AND TONIC CLONIC GENERALIZED SEIZURE PRECEDED BY HEADACHE AND NAUSEA AFTER THE ADMINISTRATION OF INTRAVENOUS HISTOACRYL FOR THE TREATMENT OF GASTRIC FUNDUS VARISCES THE VISUAL ACUITIES WERE NO LIGHT PERCEPTIONFOR BOTH EYES WITH NORMAL OCULAR FUNDUS CONTRAST BRAIN MRI SHOWED HYPOINTENS LESION ON T1 AND HYPERINTENS ON T2 ON PARIETOOCCIPITAL REGION BILATERALLY AND RIGHT POSTERIOR CORPUS CALLOSUM CORPUS WITHOUT CONTRAST ENHANCEMENT THREE DAYS AFTER HEPARINIZATION THE VISION WAS GETTING IMPROVE AND WITHIN ABOUT SEVEN DAYS HE REGAINED HIS VISION COMPLETELY